The Photochemical and Antioxidant Defence Strategies of Two Maize Genotypes Exposed to Zinc Toxicity at the Seedling Stage - Şeniz Ünalan Okar; Deniz Tanyolaç; Nuran Çiçek; Sekure Culha Erdal; Yasemin Ekmekci (Journal of Agricultural Sciences)
The main objective of the current study was to elucidate photochemical and antioxidant strategies in two maize genotypes, namely DK626 and 3223 at the early seedling stage under zinc (Zn2+) toxicity. The seedlings were grown in a controlled growth room at a temperature regime of 25±1 °C, with 40±5 % humidity, 16 h photoperiod and at 300 μmol m–2 s–1 light intensity for 8 days. Then, the seedlings were exposed to toxic zinc concentrations (2, 5 and 8 mM ZnSO4.7H2O) for 12 days. Both genotypes accumulated approximately the same amounts of Zn in leaves; however, the shoot and root lengths, and biomass decreased further in DK626 compared to 3223. The malondialdehyde content in the leaves increased gradually depending on the Zn concentrations, and the deterioration of the membrane structure was greater in DK626 compared to 3223 at highly toxic Zn levels. A reduction in photochemical activity was accompanied by non-photochemical quenching and excess energy was removed from the reaction centers by fluorescence and non-radiative inactivation in genotypes under Zn toxicity. The chlorophyll and carotenoid contents were significantly decreased, and the anthocyanin accumulation was increased with increasing Zn levels, especially in DK626. In addition, the activities of antioxidant enzymes and isoenzymes were induced at different levels in genotypes depending on the Zn toxicity level. The seedlings exposed to toxic Zn concentrations had achieved to sustain their growth by regulating their photosynthetic efficiency and their antioxidant defence system. Consequently, these genotypes could potentially be successfully used for the phytoremediation of Zn-contaminated areas. However, further studies are required to screen all growth stages for Zn tolerance capacity before making a more informed decision regarding the phytoremediation potentials of these two genotypes.